Analisa Payoff Chicken Game Theory Terkait Kebijakan Penyebaran THAAD di Korea Selatan - fadhlillah, nibras (Lampung Center for Global Studies (LCGS), 2023)
The Korean Peninsula conflict is part of the remnants of the cold war that still exists. North Korea continues to develop its nuclear weapons technology, accompanied by aggressive efforts to launch its nuclear trials continuously. On the other hand, in the face of North Korea's provocation and aggressiveness, South Korea needs to make the most probable and profitable decisions for the country's national security based on the calculation of the possible payoff in the Chicken Game Theory. This article is expected to explain South Korea's stance regarding deploying the Terminal High Altitude Area Defense (THAAD) through the use of chicken game theory analysis to prevent North Korea's nuclear weapons attack. The research method used in this article is a descriptive qualitative method with desk research or library research as the data collection technique in this study. The Korean peninsula conflict is seen as a game where a DD situation is the worst possible to happen to a country, which means a re-breaking of the Korean War. However, if we look at the situation and the actions taken by each country – North Korea and South Korea – giving in (C) is not a better choice for them than war. Therefore, both sides of the country until now continue to be on the alert by improving each country's defence and military systems.